Flame speed oscillations in combustion of two-phase mixtures - Atzler, F.; Demoulin, F.X.; Lawes, M.; Lee, Y.; Marquez, N. (Rev. Téc. Fac. Ing. Univ. Zulia)
The phenomenon of flame oscillation, the cyclic variation of flame speed during flame development, has been studied in the past in clouds of dust or droplets and even in gaseous mixtures. Although it has been addressed in the past using several approaches there is no yet a unique accepted explanation. In the present work, drop inertia effects were investigated, by comparing the experimental data with modelled predictions of oscillations in flame speed caused by the aerodynamic interaction of the gas motion ahead of the flame front with the drops. The combustion studies of nearly mono-sized drop let clouds in the present work revealed the differences between the speed of drop lets and the gas velocity near the flame front. These resulted in variations in local equivalence ratio, which in turn manifested in flame speed oscillations. For simplification a combustion vessel has been used to study the combustion of droplet clouds from a fundamental point of view, under strictly controlled (accurately established) conditions of pressure, temperature and equivalence ratio. The distribution of droplets within the mixture (spatially and in time), with out combustion, was characterised some where else.